Disaster mitigation learning integration model in social studies in middle school - Buamona, Agung Pratama; Assegaf, Abd. Rachman; Syafi’i, Imam; Sugiantoro, Sugiantoro (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2023)
Disaster management strategies will work effectively if residents have the same understanding in disaster management. The Sidoarjo Regency area is an area that has the potential for natural disasters such as floods, earthquakes and tornadoes. The purpose of this study is to increase students' knowledge, increase student awareness, develop disaster response skills. This type of research is case study research. In this study the researchers only attempted to collect simple information about disaster management in disaster preparedness schools through surveys, interviews and documentation. The integration of disaster mitigation in social sciences in junior high schools is very important to provide students with an understanding of the importance of reducing risks and losses due to disasters. The results of the study show that in general students have sufficient understanding of disasters, especially natural disasters. Students are noted to have a positive appreciation of the school. They also know that knowledge in understanding disaster is quite adequate as evidenced by the results of students' understanding related to disasters, including floods 80%, and tornadoes 75%, while other types of disasters are poorly understood (earthquakes 60%, and fires 50%). However, the existence of disaster mitigation education activities in schools is able to increase knowledge, disaster management skills and maximize self-potential, so that it has an impact on positive attitude changes in the form of increasing student awareness about disasters with an average score of 85%.